Perancangan User Interface dan User Experience Website KosIN dengan Pendekatan Design Thinking - Widhiana, Ida Bagus Ari; Astuti, Luh Gede (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 2 No 2 (2024): JNATIA Vol. 2, No. 2, Februari 2024DO - 10.24843/JNATIA.2024.v02.i02.p19, 2024)
The need for education or employment drives people to move to other areas that offer greater access to education or job opportunities. Individuals who move to a new area for higher education or job search often face challenges in finding accommodations that meet their needs. The increasing number of newcomers has led to a growing demand for housing. The main constraint is that individuals must physically go to the location to search for accommodations like boarding houses ("kos" in Indonesian). Therefore, innovation is needed by leveraging technology that can provide a solution to the challenges faced. The solution to this problem is to create a boarding house search application. The method used in this research is Design Thinking. Design Thinking aims to understand the problems and user needs, so that the developed application is truly beneficial for the users. For its testing, the Usability Testing method is used to assess to what extent a product can be used by specific users based on effectiveness, efficiency, and user satisfaction.